Summary Report of the Research Data Management Study Group - Wolf, Alan; Simpson, Mike; Salo, Dorothea; Flee, Doug; Cheetham, Jan; Barton, Bruce (My University, 2009)
The Research Data Management Study Group (RDMSG) conducted focused interviews with representatives from a number of research communities, to assess current researcher data assets, needs, and funding situations. The interviews revealed a broad diversity in asset content and format, a large number of disparate needs, and an inadequate funding base for many researchers. The study group proposes a one-year pilot project to address the most common, most urgent subset of these issues. Specific pilot pro ject activities would include partnership with between three and five campus communities in order to develop and maintain a network of distributed storage nodes, with mechanisms for au- tomated backup and archival support of data stored on them, access to storage capacity via multiple standardized protocols, and management interfaces allowing simple, flexible, researcher-controlled assignment of access management policies; and provision of consultation services to researchers attempting to preserve existing or new assets: assistance would focus on helping researchers locate existing cam- pus resources, determining appropriate metadata standards and resolving format compatibility issues, and helping to develop sustainable preservation workflows. These actions will address critical common needs of many research communities, pro- viding support that will enhance the quality and maintainability of research efforts, and alleviating the risk of losing a valuable part of the scholarly record.